2015
DOI: 10.3823/763
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Clostridium difficile infections among hospitalized patients in Amman,Jordan: A Multi-Center Study

Abstract: Objective: To evaluate the prevalence of C. difficile infection (CDI) among hospitalized patients with toxin-positive stools. Methods: This study is a multicenter study held in Jordan and focused on the prevalence of in-patients with C. difficile toxin-positive diarrhea-stools. The study included three hospitals with approximately 750 beds. In-patients charts, laboratory logbooks for in-patients with diarrhea-stool specimens were reviewed. The participating hospitals used a rapid test, which detects fecal C. d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The second important risk factor is mostly observed among the elderly population. This is most likely due to changes in the intestinal microbiota, an increased use of antibiotic and more frequent hospitalization [3,28]. Advanced age has repeatedly been found to be a risk factor for CDI.…”
Section: Risk Factors Of CDImentioning
confidence: 99%
See 3 more Smart Citations
“…The second important risk factor is mostly observed among the elderly population. This is most likely due to changes in the intestinal microbiota, an increased use of antibiotic and more frequent hospitalization [3,28]. Advanced age has repeatedly been found to be a risk factor for CDI.…”
Section: Risk Factors Of CDImentioning
confidence: 99%
“…The study showed a prevalence of toxigenic C. difficile isolates was 13.7% among adult hospitalized patients, and 73% of the C. difficile isolates carried tcdA and/or tcdB toxin genes as demonstrated by PCR and in association with diarrhea, and all C. difficile isolates were negative for binary toxin production. A recent multicenter study held in Jordan in 2015 by Wadi et al [3], detected a prevalence rate of 92.4% among hospitalized old patients with C. difficile toxin-positive diarrhea-stools using a rapid test, which detects fecal C. difficile toxins A and B. The adults and older age groups accounted for the majority of all positive cases.…”
Section: Clostridiun Difficile Infection In Arab Countriesmentioning
confidence: 99%
See 2 more Smart Citations
“…The current study indicates that there was no correlation between positive colonization of toxigenic C. difficile in infants and presence of soft stools, previous antibiotic treatment, or inflammatory bowel disease, and overall our findings were similar to that of other investigators [ 18 , 19 ]. A recent multicenter study done in three different private Jordanian hospitals in Amman over a period of 8 months showed high prevalence rate (92.4%) of positive C. difficile toxins among adults as well as older patients with a prolonged hospital stay and comorbidities [ 22 ]. Additionally, a recent study indicated that infants are widely colonized by nontoxigenic C. difficile strains and their early intestinal colonization with toxigenic strains originated from adults [ 9 ].…”
Section: Discussionmentioning
confidence: 99%